Methyl-Donor Micronutrient for Gestating Sows: Effects on Gut Microbiota and Metabolome in Offspring Piglets - He, Qin; Zou, Tiande; Chen, Jun; He, Jia; Jian, Li; Xie, Fei; You, Jinming; Wang, Zirui (Frontiers in Nutrition, 2021)
This study aimed to investigate the effects of maternal methyl-donor micronutrient supplementation during gestation on gut microbiota and fecal metabolic profile in offspring piglets. Forty-three Duroc × Erhualian gilts were assigned to two dietary groups during gestation: control diet (CON) and CON diet supplemented with MET (folic acid, methionine, choline, vitamin B6 and vitamin B12). The body weight of offspring piglets were recorded at birth and weaning. Besides, fresh fecal samples of offspring piglets were collected at 7-, 14-, and 21-day-age. The gut microbiota composition, metabolic profile, and short-chain fatty acid profiles in the fecal samples were determined using 16S rDNA sequencing, liquid chromatography-mass spectrometry (LC-MS) metabolomics, and gas chromatography method, respectively. The results show that maternal methyl-donor micronutrient supplementation increased the microbiota diversity and uniformity in feces of offspring piglets, as indicated by increased Shannon and Simpson indices at 7-day-age, and greater Simpson, ACE, Chao1 and Observed species indices at 21-day-age. Specifically, at phylum level, the relative abundance of Firmicutes, and the Firmicutes to Bacteroidetes ratio were elevated by maternal treatment. At genus level, the relative abundance of SCFA-producing Dialister, Megasphaera, and Turicibacter, lactate-producing Sharpea, as well as Akkermansia, Weissella, Pediococcus were increased in MET group. The metabolic analysis show that maternal methyl-donor micronutrient addition increased the concentrations of individual and total SCFAs of 21-day-age piglets, and increased metabolism mainly involving amino acids, pyrimidine, and purine biosynthesis. Collectively, maternal methyl-donor micronutrient addition altered gut microbiota and fecal metabolic profile, resulting in an improved weanling weight of offspring piglets.